Tips for writing (and reading) methodological articles. [article]. - Maxwell, Scott E.
One reason many methodological articles are not very intelligible to their readers is because the content is often inherently difficult. However, a contributing factor in some cases is the tacit assumption that rules of good writing cease to apply when writing about statistics. The authors of this article argue that good writing becomes even more important as the content of the article becomes more complex. Furthermore, they believe that additional rules pertain to writing methodological articles and highlight various ways that methodological article authors can make their work more accessible (and less painful) to researchers who are not methodological specialists. The --(from the author).